2022
DOI: 10.1371/journal.pgph.0000100
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prolonged hospitalization after vaginal birth in Ghana: A comparative study

Abstract: Early discharge after child delivery although indispensable, but maybe precluded by several factors. The effect of these factors on prolonged length of stay (LOS) after vaginal delivery has been sparsely investigated in Ghana. This limits understanding of potential leading indicators to inform intervention efforts and optimize health care delivery. This study examined factors associated with prolonged LOS after vaginal birth in two time-separated cohorts in Ghana. We analyzed data from Ghana’s demographic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
3
0
0
Order By: Relevance
“…The present study found maternal complications were an independent determinant of longer LOS following VD. The finding is consistent with Prior literature reports [ 29 , 34 ]. The provision of post-partum care is essential for mothers following childbirth, even more so for mothers who experience complications during labor.…”
Section: Discussionsupporting
confidence: 94%
“…The present study found maternal complications were an independent determinant of longer LOS following VD. The finding is consistent with Prior literature reports [ 29 , 34 ]. The provision of post-partum care is essential for mothers following childbirth, even more so for mothers who experience complications during labor.…”
Section: Discussionsupporting
confidence: 94%
“…Women who gave birth to big sized children were likely to stay shorter after vaginal delivery compared to those who gave birth to small and average-sized children. The ndings are in agreement with the previous studies which found that women who gave birth to children with a big weight were independently associated with a shorter length of stay compared to those who gave birth to low birth weight children [3,11,25]. This could be because small size children are often premature, which means they may have underdeveloped organs and require additional medical attention.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found maternal complication was independent determinant for longer LOS following VD. The nding is consistent with Prior literature reports [28,34]. Provision of post-partum care is essential for mothers following childbirth, even more so for mothers who experience complications during labor.…”
Section: Discussionsupporting
confidence: 91%